A Study of Factors Influencing the Development of Accommodation in Ban Wang Hora Ecotourism Community, Danchang, Suphanburi towards Sustainability under the 13th National Economic and Social Development Plan for Tourism - Phimphakanit Parisanyutanon (Asian Creative Architecture, Art and Design : ACAAD, 2025)
Thai tourism is a key driver of national economic and social development, with strategies focused on enhancing global competitiveness. It promotes income generation, cultural awareness, and sustainable preservation of local heritage, while improving community well-being and delivering experiences that foster spending and repeat visits. For this reason, the objective of this research is to study the factors influencing the development of accommodation in Ban Wang Hora Ecotourism Community, Dan Chang, Suphan Buri. The focus is on creating positive experiences for tourists and enhancing tourism value through accommodation and environmental design that aligns with the community’s unique identity. This approach corresponds with the 13th National Economic and Social Development Plan for Tourism. The study uses qualitative research methods supported by empirical analysis in the actual area, including interviews and field data collection. The research findings reveal that the key factors influencing tourists' decisions in choosing accommodations include: (1) distinctive accommodation design such as dome-shaped structures or rooms modeled after train carriages, (2) a variety of amenities, (3) Activity offerings that reflect local lifestyles and culture, (4) Understanding tourists’ behavior and needs, and (5) Promotional media that fosters engagement and long-term relationships. It is noteworthy that price is not the primary factor in accommodation booking decisions when the design and services effectively meet the target group's specific needs. This study highlights a pathway for developing accommodation models that contribute to the sustainable growth of the eco-tourism industry in terms of tourist well-being and community income generation. The findings may serve as a model for development in other areas with similar cultural and socio-geographical potential.
Keywords: Diverse Aspects of Tourism Research; Sustainability and Innovation in Business; Impulse Buying and Technology Impacts